The case study of Chácara das Rosas in Cambuquira, Minas Gerais, Brazil - Lima, Fabio; Portes, Raquel Von Randow (International Planning History Society Proceedings, 2016)
The paper discusses the issues present in the process of restoration of the old mansion named “Chácara das Rosas” in the city of Cambuquira, on the South of the state of Minas Gerais, Brazil. The project is linked to the urban rehabilitation in the proposal of master plan of the city. The comprehension is that the restoration project must be included in the general urban rehabilitation. As a reference of cultural heritage the procedures to be adopted for the restoration take into account theoretical and technical criteria for their reintegration and reuse as a public build. The work is in progress with regard to the elaboration of the restoration project linked to the master plan. Participatory process is another difficulty included considering the methodologies to develop the ideas in view of criteria of restoration. The implicit discussion allows to rethink the challenges faced in the context of small cities, particularly in Brazil, to comprehend the need for conservation as a way to preserve the local identity against the globalization process at stake. The project of restoration has been set with the proposal to a new use of the “Chácara das Rosas” in the city of Cambuquira.